ANALISIS KELAYAKAN INVESTASI INDUSTRI KARET REMAH (CRUMBRUBBER) DI WILAYAH BARAT PROVINSI ACEH - Rahmad Ramadhan; Fajri Fajri; Mustafa Usman (Universitas Teuku Umar, 2018)
Rubber farmers in Aceh especially in the South West Coast region generally have almost no relationship with the rubber processing plant and Their relationship is limited to merchants at the village level which directly conduct bokar transactions with farmers. Farmers produce bokar as if fulfill commitments with collecting merchants which almost never distinguishes the quality of bokar. The purpose of this research is to analyze the financial feasibility of developing a crumb rubber processing plant. Data processing methods and the analysis used in this research is quantitative analysis. Qualitative analysis is used to obtain a description of the feasibility aspects of the development of crumb rubber processing industry, that is financial aspect. Results of the research investment cost of crumb rubber processing factory (crumb rubber) capacity 13,200 tons per year (economic life 20 years) is suitable for use with NPV Rp. 550.695.026.000, - NBCR 1.75, IRR 53.62% and payback period 5 years 9 months. Based on sensitivity analysis of rubber plant construction capacity of 5 tons per hour, it is still possible to do this can be seen from the Net B/Caverage above 1, this shows that the construction of a rubber factory is feasible.